Risk of stomach cancer incidence in a cohort of Mayak PA workers occupationally exposed to ionizing radiation - Zhuntova, Galina V. (PLoS One, 2020)
Stomach cancer is a widespread health condition associated with environmental and genetic factors. Contribution of ionizing radiation to stomach cancer etiology is not sufficiently studied. This study was aimed to assess an association of the stomach cancer incidence risk with doses from occupational radiation exposure in a cohort of workers hired at main Mayak production association facilities in 1948–1982 taking into account non-radiation factors including digestive disorders. The study cohort comprised 22,377 individuals and by 31.12.2013 343 stomach cancer diagnoses had been reported among the cohort members. Occupational stomach absorbed doses were provided by the Mayak Worker Dosimetry System– 2008 (MWDS–2008) for external gamma ray exposure and by the Mayak Worker Dosimetry System– 2013 (MWDS–2013) for internal exposure to plutonium. Excess relative risks (ERR) per Gy for stomach cancer were estimated using the Poisson’s regression. Analyses were run using the AMFIT module of the EPICURE software. The stomach cancer incidence risk in the study cohort was found to be significantly associated with the stomach absorbed dose of gamma rays: ERR/Gy = 0.19 (95% CI: 0.01, 0.44) with a 0 year lag, and ERR/Gy = 0.20 (95% CI: 0.01, 0.45) with a 5 year lag. To estimate the baseline risk, sex, attained age, smoking status and alcohol consumption, chronic diseases (peptic ulcer, gastritis and duodenitis) were taken into account. No modifications of the radiogenic risk by non-radiation factors were found in the study worker cohort. No association of the stomach cancer incidence risk with internal exposure to incorporated plutonium was observed.